Aquatic plants as niche for lay eggs and raising juveniles by freshwater fish in three swamp habitats in South Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dharmono, Mahrudin, Irianti R, Fajeriadi H. 2022. Aquatic plants as niche for lay eggs and raising juveniles by freshwater fish in three swamp habitats in South Kalimantan, Indonesia. Biodiversitas 23: 1520-1526. Swamp is an area that is almost always waterlogged throughout the year, making it a very unique ecosystem. There is a wide variety of ecosystem services provided by swamp ecosystems, one of those is a habitat of freshwater fish, which is related to the presence of swamp vegetation. This study aimed to investigate swamp plants used as niches for freshwater fish to lay eggs and raise its offspring in three swamp areas in three regencies (i.e., Hulu Sungai Utara Regency, Tanah Laut Regency and Barito Kuala Regency) in South Kalimantan Province, Indonesia. Purposive random sampling was conducted in each swamp by observing and documenting the types of plants where fish eggs and offspring were found. We recorded 26 species of aquatic plants used by 17 species of swamp fish to lay eggs and raise offspring/fry. Eichhornia crassipes was the most widely used aquatic plant species with 100% of all freshwater fish species found (17 fish species), followed by Pistia stratiotes by 70.6% (12 fish species) and Cyperus digitatus, Lemna minor, Nelumbo nucifera, Utricularia aurea and Crinum asiaticum with each used by 52.9% (9 fish species). These plant species favored by fish need to be maintained and controlled to support the population of the fish.
Keywords: Swamp plants, stand and raise, young fish